Notions of paradigm and their value in word-formation. (July 2019) - Bauer, Laurie
Abstract : This paper explores the notion of paradigm within lexical structures, particularly, but not exclusively, morphological structures. It illustrates that the notion of paradigm includes rather more than is usually considered to fall under this heading. It also shows that, although most of the sub-types of paradigm can be found in both inflection and derivation, there are distinctions between paradigms in the two areas. In either case, their value is related to productivity and to predictability.